Behaviour of Ambient Cured Steel Fibre Reinforced Geopolymer Concrete Columns Under Axial and Flexural Loads. (August 2018) - Farhan, Nabeel A.; Sheikh, M. Neaz; Hadi, Muhammad N.S.
Abstract: This study investigates the behaviour of ambient cured geopolymer concrete column specimens reinforced with steel fibres under different loading conditions. Three types of steel fibres (straight micro steel fibre, deformed macro steel fibre and hybrid steel fibre) were used in reinforcing the geopolymer concrete column specimens. Also, geopolymer concrete column specimens without steel fibre were tested as reference column specimens. Sixteen circular geopolymer concrete column specimens of 150 mm diameter and 600 mm height were cast and tested. The influences of the addition of different types of steel fibres and the loading conditions (concentric axial load, eccentric axial load and four-point bending) on the performance of the geopolymer concrete column specimens were investigated. The test results showed that the peak axial load and bending moment of fibre reinforced geopolymer concrete column specimens were higher than those of the geopolymer concrete column specimens without steel fibres under different loading conditions. Also, the addition of different types of steel fibres resulted in significant improvements in the ductility of the geopolymer concrete column specimens. The addition of hybrid steel fibre showed the highest improvement in the peak axial load, bending moment and the ductility of ambient cured geopolymer concrete column specimens.